2017
DOI: 10.1051/0004-6361/201629744
|View full text |Cite
|
Sign up to set email alerts
|

EXTraS discovery of two pulsators in the direction of the LMC: a Be/X-ray binary pulsar in the LMC and a candidate double-degenerate polar in the foreground

Abstract: Context. The EXTraS project to explore the X-ray Transient and variable Sky searches for coherent signals in the X-ray archival data of XMM-Newton. Aims. XMM-Newton performed more than 400 pointed observations in the region of the Large Magellanic Cloud (LMC). We inspected the results of the EXTraS period search to systematically look for new X-ray pulsators in our neighbour galaxy. Methods. We analysed the XMM-Newton observations of two sources from the 3XMM catalogue which show significant signals for cohere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 59 publications
7
30
0
Order By: Relevance
“…The periods in all three optical bands are consistent to within < 3σ with the Xray period (23.63±0.02 min, Haberl et al 2017). We folded the light curves on a period of 23.6 min and show these in Figure 3.…”
Section: Ultracam Photometric Observationssupporting
confidence: 62%
See 3 more Smart Citations
“…The periods in all three optical bands are consistent to within < 3σ with the Xray period (23.63±0.02 min, Haberl et al 2017). We folded the light curves on a period of 23.6 min and show these in Figure 3.…”
Section: Ultracam Photometric Observationssupporting
confidence: 62%
“…light curves of XMMJ0510-67. The period derived from the g ′ r ′ data is entirely consistent with the X-ray period (23.63±0.03 min, Haberl et al (2017). The u ′ band data is of lower quality and the uncertainty on the period is less reliable than the g ′ r ′ estimates.…”
Section: Ultracam Photometric Observationssupporting
confidence: 58%
See 2 more Smart Citations
“…An intriguing sub-class of XRBs are the ultra luminous X-ray sources (ULXs), bright systems with isotropic luminosities that exceed the Eddington limit for a stellar mass (∼10−20 M ) BH (Kaaret et al 2017). It was initially suggested that these systems hosted intermediate-mass BHs accreting at sub-Eddington rates, but has now been established that at least a few of them host pulsating NSs (Bachetti et al 2014;Carpano et al 2018;Fürst et al 2016;Israel et al 2017). In addition, it has been shown that the spectral properties of pulsating and non pulsating ULXs share similarities and are consistent with theoretical predictions of super-Eddington accretion onto a NS (Koliopanos et al 2017;Walton et al 2018).…”
Section: Introductionmentioning
confidence: 99%